Vol. 2 : D-F; Encyclopedia of Tribology (2013, 2013)
The Encyclopedia of Tribology is the culmination of collaborative efforts among many authors, section editors, reviewers, and production editors. It is an international endeavor with authors from many countries, representing contributions from universities, industries, government laboratories, and research institutes. The Encyclopedia of Tribology would not have become a reality without the enthusiastic contributions of authors and section editors from their precious knowledge and many years of experience in the field, the careful critique by reviewers, and the detailed editing by editors of Springer. The Encyclopedia of Tribology contains 649 entries in 30 technical areas. It covers not only the traditional subjects, such as friction, wear, lubricants, and lubrication, but also topics related to biomedical and biomechanical designs, condition-based monitoring, molecular dynamics simulations, and materials science. Its scope spans from tribological science rooted in classical theories, to modern surface and interfacial engineering, from microscale contacts in components to automotive and aerospace tribology, from tribological designs to manufacturing processes, from instrumentations to testing techniques, and from analytical-numerical methods to technological innovations. In addition to the hard copy, the Encyclopedia of Tribology has an online version, which makes it dynamic and allows the team to modify and enrich its content as the field continues to evolve.